Light-diffusing silicone composition and light-diffusing material

The photodiffusion material is solved by using organopolysiloxanes of specific viscosity ranges, spherical inorganic light diffusing agents and surface-treated silica fillers in the light diffusing silicone composition and curing treatment under a catalyst. The settlement problem in storage has achieved improvements in light diffusion and heat resistance.

CN119487128APending Publication Date: 2025-02-18DOW TORAY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380051192.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-01
Filing Date
2023-07-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the long-term storage of the light-diffusing silicone composition, there is a problem of sedimentation/separation of spherical inorganic light diffusing agents, which leads to the inadequate performance of the light-diffusing material.

Method used

A combination of an organopolysiloxane having a viscosity of 100 to 1,000,000 mPa·s at 25°C, a spherical inorganic light diffuser having a specific surface area of ​​at least 50 m2/g was used. The substance is cured by organic hydrogen polysiloxane in the presence of a catalyst for hydrosilylation reaction to form a light diffusion material with excellent light diffusion properties and heat resistance.

Benefits of technology

It effectively inhibits the sedimentation and separation of spherical inorganic light diffusing agents, ensuring the long-term stability of the light diffusing material, excellent light diffusivity and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220762880000141
    Figure BDA0005220762880000141
  • Figure BDA0005220762880000151
    Figure BDA0005220762880000151
  • Figure BDA0005220762880000161
    Figure BDA0005220762880000161
Patent Text Reader

Abstract

Provided is a light-diffusing silicone composition which is capable of suppressing settling separation of a spherical inorganic light-diffusing agent over a long period of time, which can be cured by an organohydrogenpolysiloxane in the presence of a hydrosilylation reaction catalyst when an organopolysiloxane has a silicon atom-bonded alkenyl group, and which can be cured by an organohydrogenpolysiloxane when the organopolysiloxane has a silicon atom-bonded alkenyl group. After curing, a cured product having excellent light diffusivity and heat resistance is formed. The light-diffusing silicone composition according to the present invention comprises: (A) an organopolysiloxane having a viscosity of 100 to 1,000,000 mPa * s at a temperature of 25 DEG C; (B) a spherical inorganic light diffusing agent having an average particle diameter of 1-10 [mu] m; and (C) a silica filler having a specific surface area of at least 50 m2 / g as measured by the BET method, the component (C) being a silica filler that has been surface-treated with hexamethyldisilazane in advance, or a silica filler that has been surface-treated with hexamethyldisilazane in the presence of a part or all of the component (A).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a light-diffusing silicone composition and a light-diffusing material obtained by curing the composition. Background Art

[0002] In lighting and LCD backlight, light diffusion materials are used to diffuse light from a light source evenly and increase illumination. Silicone compositions that form such light diffusion materials are well known. For example, Patent Document 1 describes a curable silicone composition that includes a resinous organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in one molecule, a linear organopolysiloxane having at least two alkenyl groups bonded to silicon atoms in one molecule, an organohydrogenpolysiloxane having at least two hydrogen atoms bonded to silicon atoms in one molecule, a catalyst for hydrosilylation reaction, and a specific surface area of ​​150 m2 as measured by the BET method. 2 / g or more of fumed silica, and describes that the fumed silica may be surface-treated with hexamethyldisilazane in advance.

[0003] In addition, Patent Document 2 discloses a light-diffusing silicone rubber composition, which is prepared by adding tiny glass beads with an average particle size of 1 to 150 μm as light dispersants to a transparent or translucent uncrosslinked dimethyl silicone rubber formulation, wherein the uncrosslinked dimethyl silicone rubber formulation comprises a dimethyl polysiloxane having at least two silicon-bonded alkenyl groups in one molecule, surface-hydrophobicized or untreated fumed silica, one or more inorganic fillers selected from reinforcing or non-reinforcing inorganic fillers such as calcium carbonate, thermally conductive inorganic fillers such as titanium oxide, zinc oxide, and aluminum oxide, diphenylsilanediol, and an organic siloxane oligomer terminated with silanol groups at both ends of the molecular chain, and other wetting agents.

[0004] In addition, Patent Document 3 discloses a curable silicone composition comprising a linear organopolysiloxane having at least two silicon-bonded alkenyl groups in one molecule, a resinous organopolysiloxane having at least one silicon-bonded alkenyl group in one molecule, an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule, a catalyst for a hydrosilylation reaction, and spherical silica having an average particle size of 0.2 to 10 μm.

[0005] In recent years, research has been conducted on using spherical light diffusers such as alumina as light diffusers in light diffusing silicone compositions to improve their light diffusivity and light transmittance. However, when such silicone compositions are stored for a long time, the light diffusers precipitate / separate, and the properties of the light diffusing material obtained by curing the composition cannot be fully exerted.

[0006] On the other hand, it is known that a silica filler is added to a thermally conductive silicone rubber composition containing a large amount of a thermally conductive filler such as alumina in order to improve its properties. For example, Patent Document 4 describes a thermally conductive silicone composition comprising an organopolysiloxane, an alumina filler, a silica filler whose surface is hydrophobized with hexamethyldisilazane, an organopolysiloxane having an alkoxy group bonded to a silicon atom, and an alkoxysilane compound having an epoxy group. The composition has the characteristic that it is difficult to slide even when applied on a vertical surface.

[0007] However, in the light-diffusing silicone composition, in order not to reduce its light transmittance, the amount of light diffusing agent such as aluminum oxide is extremely small compared to the case of the thermal conductive silicone composition. In addition, in the thermal conductive silicone composition, since the balance between light diffusivity and light transmittance is not taken into consideration, it is difficult to apply the technical solutions in the thermal conductive silicone composition to the light diffusing silicone composition.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2010-018662

[0011] Patent Document 2: Japanese Patent Application Publication No. 2012-167253

[0012] Patent Document 3: Japanese Patent Application Publication No. 2015-129213

[0013] Patent Document 4: Japanese Patent Application Publication No. 2009-286855 Summary of the invention

[0014] Problems to be solved by the invention

[0015] The object of the present invention is to provide a light-diffusing silicone composition and a light-diffusing material having excellent light-diffusing properties and heat resistance, wherein the light-diffusing silicone composition can suppress the sedimentation and separation of a spherical inorganic light-diffusing agent for a long period of time, and when an organopolysiloxane has a silicon atom-bonded alkenyl group, it can be cured by an organohydrogenpolysiloxane in the presence of a catalyst for a hydrosilylation reaction, and after curing, a light-diffusing material having excellent light-diffusing properties and heat resistance is formed.

[0016] Solutions for solving problems

[0017] The light diffusing silicone composition of the present invention comprises:

[0018] (A) an organopolysiloxane having a viscosity of 100 to 1,000,000 mPa·s at 25° C.;

[0019] (B) a spherical inorganic light diffusing agent having an average particle size of 1 to 10 μm; and

[0020] (C) A specific surface area of ​​at least 50 m2 as measured by the BET method 2 / g of a silica filler, characterized in that the content of the component (B) is 30 to 85% by mass of the composition, the content of the component (C) is 0.1 to 5% by mass, and the component (C) is a silica filler that has been surface-treated with hexamethyldisilazane in advance, or a silica filler that has been surface-treated with hexamethyldisilazane in the presence of a part or all of the (A).

[0021] In the above composition, the component (B) is preferably a spherical alumina filler.

[0022] The composition preferably further contains 0.1 to 5 mass % of (D) an organosilane or organosiloxane having at least one silicon-bonded alkoxy group and at least one silicon-bonded alkenyl group or at least one epoxy-containing alkyl group in one molecule, based on the total amount of the components (A) to (C).

[0023] In the above composition, the component (A) is an organopolysiloxane having at least two silicon-bonded alkenyl groups in one molecule, and the composition further comprises:

[0024] (E) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule, wherein the amount of the silicon-bonded hydrogen atoms in the component is 0.1 to 10 mol per 1 mol of alkenyl groups in the component (A); and

[0025] (F) a catalytic amount of a catalyst for a hydrosilylation reaction,

[0026] It can be used as a curable composition.

[0027] The light-diffusing material of the present invention is characterized in that it is obtained by curing the above-mentioned curable composition.

[0028] The light diffusing material of the present invention preferably has a light transmittance of 40% or more at a wavelength of 550 nm at a thickness of 30 μm.

[0029] Effects of the Invention

[0030] The light diffusing silicone composition of the present invention is characterized in that the sedimentation separation of the spherical inorganic light diffusing agent can be suppressed for a long time, and when the organopolysiloxane has a silicon atom-bonded alkenyl group, it can be cured by the organohydrogenpolysiloxane in the presence of a catalyst for a hydrosilylation reaction, and a light diffusing material having excellent light diffusivity and heat resistance is formed after curing. In addition, the light diffusing material of the present invention has the characteristics of excellent light diffusivity and heat resistance. DETAILED DESCRIPTION

[0031] <Definition of terms>

[0032] The term "viscosity" used in this specification refers to the value at 25°C (unit: mPa·s or Pa·s) measured using a B-type rotational viscometer specified in JIS K 7117-1:1999 "Plastics - Liquid, emulsified or dispersed resins - Determination of apparent viscosity using a Brookfield rotational viscometer".

[0033] <Light-diffusing silicone composition>

[0034] First, the light diffusing silicone composition of the present invention will be described in detail.

[0035] The component (A) is an organopolysiloxane having a viscosity at 25°C in the range of 100 to 1,000,000 mPa·s, preferably in the range of 300 to 100,000 mPa·s, or in the range of 300 to 50,000 mPa·s. This is because if the viscosity at 25°C is less than the lower limit of the above range, the stability of the resulting silicone composition tends to be significantly reduced, while on the other hand, if it exceeds the upper limit of the above range, the fluidity of the resulting silicone composition tends to be significantly reduced. The molecular structure of the component (A) is not limited, and examples thereof include: linear, branched, linear with a portion of branches, and dendritic, preferably linear, linear with a portion of branches. The component (A) may be a single polymer having these molecular structures, a copolymer composed of these molecular structures, or a mixture of these polymers.

[0036] When the composition is cured by an organohydrogenpolysiloxane in the presence of a catalyst for a hydrosilylation reaction, the component (A) is an organopolysiloxane having at least two silicon-bonded alkenyl groups in one molecule. Examples of the silicon-bonded alkenyl groups in the component (A) include alkenyl groups having 2 to 12 carbon atoms such as vinyl, allyl, butenyl, pentenyl, and hexenyl, preferably vinyl. In addition, as the group bonded to the silicon atom other than the alkenyl group in the component (A), for example, there can be shown: alkyl groups having 1 to 12 carbon atoms such as methyl, ethyl, propyl, butyl, pentyl, and hexyl; cycloalkyl groups having 5 to 12 carbon atoms such as cyclopentyl and cyclohexyl; aryl groups having 6 to 12 carbon atoms such as phenyl, tolyl, and xylyl; aralkyl groups having 7 to 12 carbon atoms such as benzyl and phenethyl; halogenated alkyl groups having 1 to 12 carbon atoms such as 3,3,3-trifluoropropyl and 3-chloropropyl, preferably alkyl groups and aryl groups, and particularly preferably methyl and phenyl groups. It should be noted that in order to cure the composition by a hydrosilylation reaction, when the composition contains an organohydrogenpolysiloxane, the component (A) does not have a silicon-bonded hydrogen atom, and when the composition contains the following component (D), it does not have a silicon-bonded alkoxy group or an epoxy-containing alkyl group.

[0037] Examples of the organopolysiloxane of the component (A) include dimethyl polysiloxane terminated with dimethyl vinyl siloxane groups at both ends of the molecular chain, dimethyl polysiloxane terminated with methyl phenyl vinyl siloxane groups at both ends of the molecular chain, dimethyl siloxane-methyl phenyl siloxane copolymer terminated with dimethyl vinyl siloxane groups at both ends of the molecular chain, dimethyl siloxane-methyl vinyl siloxane copolymer terminated with dimethyl vinyl siloxane groups at both ends of the molecular chain, trimethyl siloxane-methyl vinyl siloxane copolymer terminated with trimethyl siloxane groups at both ends of the molecular chain, methyl (3,3,3-trifluoropropyl) polysiloxane terminated with dimethyl vinyl siloxane groups at both ends of the molecular chain, dimethyl siloxane-methyl vinyl siloxane copolymer terminated with silanol groups at both ends of the molecular chain, dimethyl siloxane-methyl vinyl siloxane-methyl phenyl siloxane copolymer terminated with silanol groups at both ends of the molecular chain, and polysiloxanes having the formula: (CH3)3SiO 1 / 2 The siloxane unit shown is represented by the formula: (CH3)2(CH2=CH)SiO 1 / 2 The siloxane unit shown is represented by the formula: CH3SiO 3 / 2 The siloxane unit shown and the formula: (CH3)2SiO 2 / 2 The copolymers are composed of siloxane units as shown.

[0038] The component (B) is a spherical inorganic light diffuser for imparting light diffusivity to the composition. Examples of the component (B) include spherical silica fillers and spherical alumina fillers, preferably spherical alumina fillers. The average particle size of the component (B) is in the range of 1 to 10 μm, preferably in the range of 2 to 5 μm. The average particle size is, for example, d measured by the Coulter method or the laser diffraction scattering method. 50 The value of .

[0039] The content of component (B) is in the range of 30 to 85% by mass, preferably in the range of 50 to 85% by mass, or in the range of 60 to 80% by mass, relative to the total amount of components (A) to (C). This is because if the content of component (B) is greater than the lower limit of the above range, the light dispersibility of the resulting composition is improved, while on the other hand, if the content of component (B) is less than the upper limit of the above range, the light transmittance of the resulting composition is improved.

[0040] The component (C) is a silica filler, which is used to suppress the sedimentation / separation of the component (B) and stabilize the properties of the composition even when the composition is stored for a long time. The specific surface area of ​​the component (C) measured by the BET method is 50 m 2 / g or more, preferably 100m 2 / g or above, or 200m 2 On the other hand, the upper limit of the specific surface area is not particularly limited, but is preferably 500 m / s from the viewpoint of dispersibility with the component (A) and sufficient suppression of sedimentation / separation of the component (B). 2 / g or less, or 400m 2 / g or less.

[0041] The composition is characterized in that component (C) is a silica filler that has been surface-treated in advance with hexamethyldisilazane, or a silica filler that has been surface-treated with hexamethyldisilazane in the presence of part or all of (A). As such a silica filler that has been surface-treated in advance with hexamethyldisilazane, RDX200 manufactured by Japan Aerosil Co., Ltd. can be purchased. In addition, the untreated silica filler can be added to component (A) after being surface-treated in a hexamethyldisilazane solution. In addition, the untreated silica filler can also be added to component (A) and then surface-treated in situ with hexamethyldisilazane.

[0042] The content of component (C) is in the range of 0.1 to 5% by mass, preferably in the range of 0.1 to 3% by mass, or in the range of 0.1 to 1% by mass, relative to the total amount of components (A) to (C). This is because if the content of component (B) is above the lower limit of the above range, the sedimentation / separation of component (B) can be fully suppressed, and on the other hand, if it is below the upper limit of the above range, the light transmittance of the obtained composition can be improved.

[0043] In the composition, when the affinity of component (B) with respect to component (A) is improved and the composition is applied to an optical member, as an optional component for improving its adhesion, an organic silane or organic siloxane (D) having at least one silicon atom-bonded alkoxy group and at least one silicon atom-bonded alkenyl group or at least one epoxy-containing alkyl group in one molecule may be contained.

[0044] In such component (D), examples of the organosilane or organosiloxane having at least one silicon atom-bonded alkoxy group and at least one silicon atom-bonded alkenyl group in one molecule include those represented by the general formula:

[0045] R 2 S i 1 a (OR 3 ) 3-a

[0046] The organoalkoxysilane shown is represented by the general formula:

[0047] R 1 2R 2 SiO(R 1 2SiO) n S i 1 a (OR 3 ) 3-a

[0048] The organosiloxane shown.

[0049] In the above formula, R 1 It is an alkyl group having 1 to 12 carbon atoms, and specific examples thereof include methyl group, ethyl group, propyl group, butyl group, pentyl group, and hexyl group, and is preferably a methyl group.

[0050] In addition, in the above formula, R 2 The alkenyl group has 2 to 12 carbon atoms. Specific examples thereof include vinyl, allyl, butenyl, pentenyl and hexenyl. Preferably, the vinyl group is included.

[0051] In addition, in the above formula, R 3 It is an alkyl group having 1 to 3 carbon atoms, and specific examples thereof include a methyl group, an ethyl group, and a propyl group, and a methyl group is preferred.

[0052] In addition, in the above formula, a is 0, 1 or 2, preferably 0.

[0053] In addition, in the above formula, n is an integer from 0 to 10, preferably an integer from 0 to 5.

[0054] On the other hand, in the component (D), as the organosilane or organosiloxane having at least one silicon atom-bonded alkoxy group and at least one epoxy group-containing alkyl group in one molecule, examples include: 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(2,3-epoxycyclohexyl)ethyltrimethoxysilane, 2-(2,3-epoxycyclohexyl)ethylmethyldimethoxysilane and other organoalkoxysilanes, and the average unit formula:

[0055] (R 1 R 2 SiO 2 / 2 ) b (R 4 SiO 3 / 2 ) c (R 1 2SiO 2 / 2 ) d (R 3 O 1 / 2 ) e

[0056] The organopolysiloxane shown.

[0057] In the above formula, R 1 ~R 3 Is the same as above.

[0058] In addition, in the above formula, R 4 Is an epoxy group-containing alkyl group. Specifically, examples include: glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl; epoxycyclohexylalkyl groups such as 2-(2,3-epoxycyclohexyl)ethyl and 3-(2,3-epoxycyclohexyl)propyl.

[0059] In addition, in the above formula, b, c, d are numbers that satisfy 0 < b ≤ 0.4, 0 < c ≤ 0.5, 0 < d ≤ 0.6, 0 < e ≤ 0.5, and b + c + d = 1.0, respectively.

[0060] The content of component (D) is 0.1 to 5% by mass, preferably 0.2 to 5% by mass or 0.2 to 3% by mass, relative to the total amount of components (A) to (C). This is because if the content of component (D) is above the lower limit of the above range, the affinity of component (B) to component (A) can be improved, thereby contributing to suppressing the sedimentation / separation of component (B), and on the other hand, if it is below the upper limit of the above range, the adhesion between the obtained composition and the optical member can be improved.

[0061] The composition can be made into a curable composition by further blending an organic peroxide, an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms, and a catalyst for hydrosilylation reaction of a platinum group metal as a curing agent. When the composition is cured by hydrosilylation reaction, the component (A) is an organopolysiloxane having at least two alkenyl groups bonded to carbon atoms in one molecule, and further contains (E) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule and (F) a catalyst for hydrosilylation reaction.

[0062] The component (E) is an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule. As the group bonded to the silicon atom in the component (E), for example, there can be shown: alkyl groups having 1 to 12 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, and hexyl; cycloalkyl groups having 5 to 12 carbon atoms, such as cyclopentyl and cyclohexyl; aryl groups having 6 to 12 carbon atoms, such as phenyl, tolyl, and xylyl; aralkyl groups having 7 to 12 carbon atoms, such as benzyl and phenethyl; halogenated alkyl groups having 1 to 12 carbon atoms, such as 3,3,3-trifluoropropyl and 3-chloropropyl; preferably alkyl groups and aryl groups, and particularly preferably methyl and phenyl groups. It should be noted that the component (B) does not have a silicon-bonded alkenyl group to prevent self-crosslinking by a hydrosilylation reaction, and when the composition has the above-mentioned component (D), it does not have a silicon-bonded alkoxy group or an epoxy-containing alkyl group. The viscosity of the component (E) at 25°C is not limited, but is preferably in the range of 1 to 100,000 mPa·s or 1 to 5,000 mPa·s. The molecular structure of the component (F) is not limited, and examples thereof include linear, branched, linear with a portion of branches, cyclic, and dendritic structures. The component (E) may be a single polymer having these molecular structures, a copolymer composed of these molecular structures, or a mixture thereof.

[0063] Examples of the organohydrogen polysiloxane of the component (E) include dimethyl polysiloxane terminated with dimethyl hydrogen siloxane groups at both ends of the molecular chain, dimethyl siloxane-methyl hydrogen siloxane copolymer terminated with trimethyl siloxane groups at both ends of the molecular chain, dimethyl siloxane-methyl hydrogen siloxane copolymer terminated with dimethyl hydrogen siloxane groups at both ends of the molecular chain, and dimethyl siloxane-methyl hydrogen siloxane copolymer terminated with dimethyl hydrogen siloxane groups at both ends of the molecular chain.1 / 2 The siloxane unit shown, formula: (CH3)2HSiO 1 / 2 The siloxane unit shown and the formula: SiO 4 / 2 The organosiloxane copolymers are composed of siloxane units as shown.

[0064] The content of the component (E) is in the range of 0.1 to 10 mol, or in the range of 0.5 to 5 mol, of the silicon-bonded hydrogen atoms in the component (A) relative to 1 mol of the silicon-bonded alkenyl groups. This is because if the content of the component (E) is at least the lower limit of the above range, the obtained composition will be sufficiently cured, while if it is at most the upper limit of the above range, the heat resistance of the light diffusion material obtained by curing the composition will be good.

[0065] (F) component is a catalyst for hydrosilylation reaction for promoting the curing of the composition, and examples thereof include: platinum catalysts, rhodium catalysts, and palladium catalysts. In particular, from the viewpoint of significantly promoting the curing of the composition, (F) component is preferably a platinum catalyst. As platinum catalysts, examples thereof include: platinum fine powder, chloroplatinic acid, alcohol solution of chloroplatinic acid, alkenyl siloxane complex of platinum, olefin complex of platinum, and carbonyl complex of platinum, preferably alkenyl siloxane complex of platinum.

[0066] The content of the component (F) is a catalytic amount and is not particularly limited. The amount of the platinum metal is preferably in the range of 0.01 to 1,000 ppm, 0.1 to 500 ppm, 5 to 500 ppm, 0.1 to 300 ppm, or 5 to 300 ppm in terms of mass relative to the component (A). This is because if the content of the component (F) is above the lower limit of the above range, curing of the composition is promoted, while if it is below the upper limit of the above range, the obtained cured product is less likely to cause problems such as coloring.

[0067] In addition, the composition may contain (G) a hydrosilylation reaction inhibitor for adjusting its curability and usable time. Examples of the (G) component include: 1-ethynyl-cyclohexane-1-ol, 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, and 2-phenyl-3-butyn-2-ol, alkynols such as 3-methyl-3-pentene-1-yne and 3,5-dimethyl-3-hexene-1-yne, and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane. alkane, 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane and other alkenyl-containing siloxane oligomers; other hydrazines, triazoles, phosphines, thiols, organic nitrogen compounds, acetylene alcohols, silylated acetylene alcohols, maleic acid, fumaric acid, olefinic or aromatic unsaturated amides, olefinic unsaturated isocyanates, olefinic silanes, olefinic siloxanes, unsaturated hydrocarbon monoesters and diesters, hydroperoxides, nitriles, diaziridines. The content of component (G) is not particularly limited, but is preferably in the range of 0.0001 to 5 parts by mass relative to 100 parts by mass of the composition.

[0068] Furthermore, in the above-mentioned composition, an organic solvent, a thickener, a heat-resistant additive, a dye, a pigment, and a flame retardant may be blended as other optional components within a range not impairing the purpose of the present invention.

[0069] In particular, by diluting the composition with an organic solvent, the composition can be applied to an optical member to impart light diffusing properties to the optical member. The organic solvent is not particularly limited, and examples thereof include non-halogen solvents such as isopropanol, tert-butyl alcohol, cyclohexanol, cyclohexanone, methyl ethyl ketone, methyl isobutyl ketone, toluene, xylene, mesitylene, 1,4-dioxane, dibutyl ether, anisole, 4-methylanisole, ethylbenzene, ethoxybenzene, ethylene glycol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 2-methoxyethanol (ethylene glycol monomethyl ether), diethylene glycol dimethyl ether, diethylene glycol monomethyl ether, ethyl acetate, butyl acetate, propyl propionate, 1-methoxy-2-propyl acetate, 1-ethoxy-2-propyl acetate, octamethylcyclotetrasiloxane, and hexamethyldisiloxane; and halogen solvents such as trifluoromethylbenzene, 1,2-bis(trifluoromethyl)benzene, 1,3-bis(trifluoromethyl)benzene, 1,4-bis(trifluoromethyl)benzene, trifluoromethylchlorobenzene, trifluoromethylfluorobenzene, and hydrofluoroether. These organic solvents may be used alone or in combination of two or more.

[0070] In addition, the coating method is not limited, and examples thereof include gravure coating, offset coating, indirect gravure, roll coating using an offset rotogravure roll coater, reverse roll coating, air knife coating, curtain coating using a curtain flow coater, comma blade coating, Mayer Bar, and spin coating.

[0071] <Light diffusion material>

[0072] Next, the light diffusing material of the present invention will be described in detail.

[0073] The light-diffusing material of the present invention is obtained by curing the above-mentioned curable composition.

[0074] The light diffusion material of the present invention preferably has a light transmittance of 40% or more at a wavelength of 550 nm when the thickness (i.e., the optical path length) is 30 μm. The light transmittance is a value measured by an ultraviolet-visible-near-infrared spectrophotometer equipped with an integrating stage unit of 150 mm in diameter for the wavelength region of visible light (the entire range). Furthermore, the light diffusion material preferably has the following light diffusivity: the light scattering characteristics are measured using a scattering profiler or the like equipped with a white light source (especially a white LED through a combination of a blue LED and a yellow phosphor), and in its bidirectional transmittance distribution function, when the straight-through transmission light intensity is set to 1, the transmission light intensity at the light receiving position inclined 45 degrees relative to the straight-through transmission light with the measurement sample as the center is 0.65 or more. It should be noted that the bidirectional transmittance distribution function (BTDF) is a function inherent to the transmission position that indicates to what extent the light component is transmitted and travels in each direction when light is incident at a certain position from a certain direction.

[0075] In addition, the hardness of the light diffuser of the present invention is not limited, but its Shore D hardness is preferably in the range of 30 to 80. The hardness can be adjusted by the content of the component (B) in the above composition and the crosslinking density based on the hydrosilylation reaction of the components (A) and (E). The light diffuser of the present invention is suitable as a sheet-like light diffuser having flexibility.

[0076] In addition, the light diffusion material of the present invention may also be in a state of being laminated on the surface of a film-like or sheet-like optical component. The film thickness of the light diffusion material in such a laminate is not particularly limited, but from the balance between light transmittance and light diffusion, the film thickness is preferably in the range of 5 to 2000 μm, in the range of 100 to 1000 μm, in the range of 100 to 500 μm, or in the range of 20 to 300 μm.

[0077] Example

[0078] Hereinafter, the light diffusing silicone composition and the light diffusing material of the present invention are described in detail by way of examples. It should be noted that the present invention is not limited to these examples. In addition, in the formula, Me, Vi, and Ep represent methyl, vinyl, and 3-glycidyloxypropyl, respectively. In addition, the viscosity in the examples is a value at 25°C measured using a digital display B-type rotational viscometer (Vismetron VDA2 manufactured by Shibaura Systems Co., Ltd.) specified in JIS K 7117-1:1999 "Plastics-Liquid, emulsified or dispersed resins-Determination of apparent viscosity using a Brookfield type rotational viscometer". In addition, the thickness of the light diffusing material is measured using a film thickness meter (manufactured by Nikon, DIGIMICRO MFC-101A).

[0079] <Example 1-2, Comparative Example 1-2>

[0080] The following components were uniformly mixed to prepare a light diffusing silicone composition so as to have the composition (parts by mass) shown in Table 1. Specifically, component (c1), component (c3) or component (c4) was added to a mixture of component (a1), component (a2), component (a3), component (d1), component (d2) and component (d3), and then component (f1), component (g1) and component (b1) were added and uniformly mixed to prepare a light diffusing silicone composition.

[0081] As (A) component, the following components were used.

[0082] (a1): A white solid at 25°C having the average unit formula:

[0083] (Me3SiO 1 / 2 ) 0.34 (Me2ViSiO 1 / 2 ) 0.11 (SiO 4 / 2 ) 0.55

[0084] The organopolysiloxane containing a vinyl group of 36% by mass and having a viscosity of 9,000 mPa·s is given by the formula:

[0085] Me2ViSiO(Me2SiO) 530 SiMe2Vi

[0086] An organopolysiloxane mixture having a viscosity of 21,000 mPa·s and composed of 64% by mass of dimethyl polysiloxane as shown

[0087] (a2): The viscosity is 2,000 mPa·s, according to the formula:

[0088] Me2ViSiO(Me2SiO) 310 SiMe2Vi

[0089] Dimethylpolysiloxane

[0090] (a3): The viscosity is 400 mPa·s, according to the formula:

[0091] Me2ViSiO(Me2SiO) 150 SiMe2Vi

[0092] Dimethylpolysiloxane

[0093] As (B) component, the following components were used.

[0094] (b1): Spherical alumina filler with an average particle size of 4 μm (AZ4-10 manufactured by Nippon Steel Chemical Materials Co., Ltd.)

[0095] As (C)component, the following components were used.

[0096] (c1): Surface treated with hexamethyldisilazane, with a specific surface area of ​​115 to 165 m2 as measured by the BET method 2 / g hydrophobic fumed silica particles (RX200 manufactured by Japan Aerosil Co., Ltd.)

[0097] (c2): In component (A), the specific surface area measured by the BET method was reduced to 200 m 2 / g of fumed silica particles (Aerosil 200 manufactured by Japan Aerosil Co., Ltd.) surface-treated silica particles (the preparation method is described in Example 3 below)

[0098] In addition, as a comparison of the component (C), the following components were used.

[0099] (c3): BET specific surface area is 200m 2 / g of fumed silica particles (Aerosil 200 manufactured by Japan Aerosil Co., Ltd.)

[0100] (c4): Hydrophobic fumed silica fine particles surface-treated with dimethyldichlorosilane (Reolosil DM30S manufactured by Tokuyama Co., Ltd.)

[0101] As (D)component, the following components were used.

[0102] (d1): By the formula:

[0103] Me2ViSiO(Me2SiO)3Si(OMe)3

[0104] Dimethylsiloxane oligomers shown

[0105] (d2): From the average unit formula:

[0106] (MeViSiO 2 / 2 ) 0.225 (EpSiO 3 / 2 ) 0.311 (Me2SiO 2 / 2 ) 0.464 (MeO 1 / 2 ) 0.01~0.5

[0107] The organopolysiloxane containing 3-glycidyloxypropyl group shown

[0108] (d3): 3-glycidyloxypropylmethyldiethoxysilane

[0109] As the (F) component, the following components were used.

[0110] (f1): 1,3-divinyltetramethyldisiloxane solution of platinum complex (platinum content 4,000 ppm)

[0111] As (G) component, the following components were used.

[0112] (g1) 3,5-Dimethyl-1-hexyn-3-ol

[0113] <Example 3>

[0114] The above components were uniformly mixed to obtain the composition (parts by mass) shown in Table 1 to prepare a light diffusing silicone composition. Specifically, 100 parts by mass of component (a2), 6 parts by mass of hexamethyldisilazane, and a silica gel having a specific surface area of ​​200 m2 as measured by the BET method were mixed. 2After 40 parts by weight of fumed silica particles (Aerosil 200 manufactured by Japan Aerosil Co., Ltd.) of 1.34 g / g were uniformly mixed, 2 parts by weight of water were added, the mixture was further mixed, and the mixture was heated and mixed at 170°C for 1 hour under reduced pressure, and then cooled to room temperature to prepare a silicone base material. In addition, the silica particles surface-treated with hexamethylsilazane in the silicone base material were used as component (c2). Then, component (a1), the remaining component (a2), component (a3), component (d1), component (d2) and component (d3) were added to the silicone base material, and then component (f1), component (g1) and component (b1) were added and uniformly mixed to prepare a light-diffusing silicone composition.

[0115] <Comparative Example 3>

[0116] The above components were uniformly mixed to obtain the composition (parts by mass) shown in Table 1, thereby preparing a light diffusing silicone composition. Specifically, the components (f1), (g1) and (b1) were added to a mixture of the components (a1), (a2), (a3), (d1), (d2) and (d3), and the mixture was uniformly mixed to prepare a light diffusing silicone composition.

[0117] <Appearance of the light-diffusing silicone composition>

[0118] The light diffusing silicone compositions of Examples 1-3 and Comparative Examples 1-3 were placed in a transparent glass bottle and left to stand at 25° C. After a predetermined period of time, the surface of the composition removed due to sedimentation / separation of the component (b1) was observed and evaluated as follows.

[0119] ○: No clear layer was observed on the surface of the composition.

[0120] Δ: A transparent layer was slightly observed on the surface of the composition.

[0121] ×: A transparent layer was observed on the surface of the composition.

[0122] <Viscosity of Light Diffusing Silicone Composition>

[0123] The light diffusing silicone compositions of Examples 1-3 and Comparative Examples 1-3 were placed in a transparent glass bottle and left to stand at 25° C. After a predetermined period of time, the composition near the surface was collected with a spatula and its viscosity was measured using a rheometer MCR301 manufactured by Anton Paar. The results are shown in Table 1.

[0124] [Table 1]

[0125]

[0126]

[0127] ※The viscosity cannot be measured due to unevenness.

[0128] It can be seen from the results in Table 1 that the light-diffusing silicone compositions of Examples 1-3 show very little sedimentation / separation of component (B) after long-term storage. In contrast, the light-diffusing silicone composition of Comparative Example 3 shows sedimentation and separation of component (B) as early as after one month of storage, indicating a lack of stability.

[0129] <Example 4-6, Comparative Example 4-6>

[0130] The light diffusing silicone compositions prepared in Examples 1-3 and Comparative Examples 1-3 were further uniformly mixed with the following component (E) to obtain the composition (parts by mass) shown in Table 2, thereby preparing a curable light diffusing silicone composition. It should be noted that the amount of the component (E) was 1 mol of silicon-bonded hydrogen atoms in the component (E) per 1 mol of silicon-bonded alkenyl groups in the component (A).

[0131] As the (E) component, the following components were used.

[0132] (e1): By formula:

[0133] Me3SiO(MeHSiO) 50 SiMe3

[0134] The methyl hydrogen polysiloxane shown in the figure has trimethylsiloxane groups at both ends of the molecular chain

[0135] [Production of 30 μm thick cured product]

[0136] 9 g of propyl propionate was added to 60 g of the curable light diffusing silicone composition of Example 4-6 and Comparative Example 4-6, and uniformly stirred while degassing to prepare a coating agent. The obtained coating agent was applied to D263Teco glass (77 mm×77 mm×0.2 mm) manufactured by SHOT using a 75 μm thick applicator, and then heated in an oven at 150° C. for 1 hour to prepare a glass integrated body consisting of a cured product with a thickness of 30 μm.

[0137] [Transmittance of cured product]

[0138] Install on the above glass integration The total light transmittance of the integrating sphere unit was measured using an ultraviolet-visible-near-infrared spectrophotometer (V-770 manufactured by JASCO Corporation). A value of 45% or more was considered good transmittance and was indicated by "◎" in Table 2.

[0139] [Heat resistance of cured product]

[0140] In addition, the glass monolith was heated at 160 to 200° C. for 3 minutes using a reflow soldering device RDT-250C manufactured by Malcom, and then rapidly heated and maintained at 260° C. or higher for 10 seconds, and then air-cooled to 150° C. This operation was repeated 3 times, and the change ratio relative to the initial value of the transmittance at a wavelength of 550 nm was obtained. The case of less than 0.5% was indicated by "◎" as good heat resistance, and the case of more than 0.5% was indicated by "×" as poor heat resistance.

[0141] <Light Diffusivity of Cured Material>

[0142] The light transmission and scattering of the above-mentioned glass integrated body was measured using Genesia Gonio / Far Filed Profiler manufactured by Genesia. When the transmitted light intensity of white light incident perpendicularly to the measurement sample surface, that is, the linear transmitted light intensity, was set to 1 using the 45-degree bidirectional transmittance distribution function, the case where the light receiving intensity at a position where the light receiving unit was inclined 45 degrees relative to the incident light axis with the measurement sample as the center was 0.65 or more was considered to have good light diffusion and was indicated by "◎".

[0143] <Shore D hardness of cured product>

[0144] The curable light diffusing silicone compositions of Examples 4-6 and Comparative Examples 4-6 were degassed, and then heated in a press at 125° C. for 15 minutes using a mold having a width of 10 mm, a length of 50 mm, and a thickness of 2 mm, and then heated in an oven at 150° C. for 1 hour to prepare a cured product. Three sheets of the cured product were stacked using an automatic rubber hardness tester P2 manufactured by Polymer Meter to measure the Shore D hardness.

[0145] [Table 2]

[0146]

[0147]

[0148] Industrial Applicability

[0149] The light-diffusing silicone composition of the present invention can suppress the sedimentation and separation of the light-diffusing spherical filler for a long time, and when the organopolysiloxane has a silicon atom-bonded alkenyl group, it can be cured by the organohydrogenpolysiloxane in the presence of a catalyst for a hydrosilylation reaction to form a light-diffusing material with excellent light diffusivity and heat resistance after curing. Therefore, it is suitable as a coating agent for forming a light-diffusing material for lighting and LCD backlight.

Claims

1. A light-diffusing silicone composition, comprising: (A) an organopolysiloxane having a viscosity of 100 to 1,000,000 mPa·s at 25° C.; (B) a spherical inorganic light diffusing agent having an average particle size of 1 to 10 μm; and (C) A specific surface area of ​​at least 50 m2 as measured by the BET method 2 / g of silica filler, It is characterized in that Relative to the total amount of the components (A) to (C), the content of the component (B) is 30 to 85% by mass of the composition, and the content of the component (C) is 0.1 to 5% by mass. The component (C) is a silica filler that has been surface-treated with hexamethyldisilazane in advance, or a silica filler that has been surface-treated with hexamethyldisilazane in the presence of a part or all of the component (A).

2. The light diffusing silicone composition according to claim 1, wherein Component (B) is a spherical alumina filler.

3. The light diffusing silicone composition according to claim 1, further comprising 0.1 to 5% by mass of (D) an organosilane or organosiloxane having at least one silicon atom-bonded alkoxy group and at least one silicon atom-bonded alkenyl group or at least one epoxy-containing alkyl group in one molecule, relative to the total amount of the components (A) to (C).

4. The light diffusing silicone composition according to claim 1, wherein The component (A) is an organopolysiloxane having at least two silicon-atom-bonded alkenyl groups in one molecule, and the light-diffusing silicone composition further comprises: (E) an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in one molecule, wherein the amount of the silicon-bonded hydrogen atoms in the component is 0.1 to 10 mol per 1 mol of alkenyl groups in the component (A); and (F) A catalytic amount of a catalyst for a hydrosilylation reaction. 5 . A light diffusing material, which is obtained by curing the light diffusing silicone composition according to claim 4 .

6. The light diffusion material according to claim 5, wherein At a thickness of 30 μm, the light transmittance at a wavelength of 550 nm is 40% or more.

Citation Information

Patent Citations

  • Thermally-conductive silicone composition and electronic device

    JP2009286855A

  • Liquid silicone rubber composition for optical waveguide plate

    JP2010018662A

  • Light-diffusive dimethylsilicone rubber composition

    JP2012167253A

  • Addition-curing type silicone rubber composition

    JP2015129213A